2020
DOI: 10.1136/jnnp-2020-323870
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects and acceptability of non-invasive brain stimulation on Alzheimer’s disease and mild cognitive impairment: a component network meta-analysis

Abstract: ObjectivesTo compare cognitive effects and acceptability of repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) in patients with Alzheimer’s disease (AD) or mild cognitive impairment (MCI), and to determine whether cognitive training (CT) during rTMS or tDCS provides additional benefits.MethodsElectronic search of PubMed, Medline, Embase, the Cochrane Library and PsycINFO up to 5 March 2020. We enrolled double-blind, randomised controlled trials (RCTs). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 39 publications
4
97
2
Order By: Relevance
“…Recent rTMS protocols have proposed the combination of rTMS and cognitive training, and our results also provide evidence to the improvement effect of the combination of rTMS and cognitive training on the cognitive performance (Bentwich et al, 2011;Das et al, 2019;Chu et al, 2020). It has been proposed that rTMS trials with cognitive training would combine the "exogenous" and "endogenous" stimulation to enhance neuroplasticity, in which the rTMS may be capable of pre-activating the initial state of neural system and the subsequent cognitive training would interact with the ongoing brain activation to potentiate or generalize the related neural impact (Miniussi and Rossini, 2011;Miniussi and Vallar, 2011;Bagattini et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Recent rTMS protocols have proposed the combination of rTMS and cognitive training, and our results also provide evidence to the improvement effect of the combination of rTMS and cognitive training on the cognitive performance (Bentwich et al, 2011;Das et al, 2019;Chu et al, 2020). It has been proposed that rTMS trials with cognitive training would combine the "exogenous" and "endogenous" stimulation to enhance neuroplasticity, in which the rTMS may be capable of pre-activating the initial state of neural system and the subsequent cognitive training would interact with the ongoing brain activation to potentiate or generalize the related neural impact (Miniussi and Rossini, 2011;Miniussi and Vallar, 2011;Bagattini et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Meta-analysis studies revealed that high-frequency rTMS treatment positively affected cognitive function and global impression ( Cheng et al, 2018 ; Dong et al, 2018 ; Lin et al, 2019 ). Another recent meta-analysis also revealed that compared with sham brain stimulation, high-frequency rTMS had short-term and long-term (lasting to 1 month after treatment) positive effects on the general cognition of AD patients ( Chu et al, 2021 ). More concretely, significant improvements were found on language, including the accuracy of action naming and auditory sentence comprehension ( Cotelli et al, 2006 , 2008 , 2011 ; Zhao et al, 2017 ), verbal and non-verbal agility ( Devi et al, 2014 ), memory ( Haffen et al, 2012 ; Zhao et al, 2017 ; Chu et al, 2021 ), and attention ( Eliasova et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…6,26 Although a specific protocol has not been identified for rTMS for AD, most studies have investigated placement over the front of the head -specifically, the dorsolateral prefrontal cortex -based on the protocol for multiple depressive disorder, with high, theta, or low-frequencies. 26,27 The most commonly used clinical protocols also involve an application for 20 to 40 minutes over a period of 2 to 5 weeks. 27 For short-term cognitive effects, high frequency rTMS has demonstrated positive results, although whether the results are clinically meaningful is uncertain.…”
Section: Repetitive Transcranial Magnetic Stimulationmentioning
confidence: 99%